Exciton-related nonlinear optical properties in cylindrical quantum dots with asymmetric axial potential : combined effects of hydrostatic pressure, intense laser field, and applied electric field (2012)
ABSTRACT: The exciton binding energy of an asymmetrical GaAs-Ga1−xAlxAs cylindrical quantum dot is studied with the use of the effective mass approximation and a variational calculation procedure. The influence on this quantity of the application of a direct-current electric field along the growth direction of the cylinder, together with that of an intense laser field, is particularly considered. The resulting states are used to calculate the exciton-related nonlinear optical absorption and optical rectification, whose corresponding resonant peaks are reported as functions of the external probes, the quantum dot dimensions, and the aluminum molar fraction in the potential barrier regions.